2010
DOI: 10.1186/1756-8722-3-8
|View full text |Cite
|
Sign up to set email alerts
|

From basic research to clinical development of MEK1/2 inhibitors for cancer therapy

Abstract: The Ras-dependent Raf/MEK/ERK1/2 mitogen-activated protein (MAP) kinase signaling pathway is a major regulator of cell proliferation and survival. Not surprisingly, hyperactivation of this pathway is frequently observed in human malignancies as a result of aberrant activation of receptor tyrosine kinases or gain-of-function mutations in RAS or RAF genes. Components of the ERK1/2 pathway are therefore viewed as attractive candidates for the development of targeted therapies of cancer. In this article, we briefl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
156
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(163 citation statements)
references
References 99 publications
(113 reference statements)
2
156
0
1
Order By: Relevance
“…Among the four major MAPK pathways, MEK1/2 has been shown to activate only ERK1/2, a major regulator of cell proliferation, survival, differentiation, motility, and angiogenesis that is activated by many growth factors and cytokines through activation of all three receptor classes (11). We found that the MEK inhibitor U0126, identified in our primary screen as a sprouting inhibitor, blocked lymphangiogenic sprouting in a dose-dependent manner with a minimal effective concentration of 1 μM.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Among the four major MAPK pathways, MEK1/2 has been shown to activate only ERK1/2, a major regulator of cell proliferation, survival, differentiation, motility, and angiogenesis that is activated by many growth factors and cytokines through activation of all three receptor classes (11). We found that the MEK inhibitor U0126, identified in our primary screen as a sprouting inhibitor, blocked lymphangiogenic sprouting in a dose-dependent manner with a minimal effective concentration of 1 μM.…”
Section: Discussionmentioning
confidence: 74%
“…Our finding that U0126 potently inhibited adult lymphangiogenesis in an established in vivo assay that partially mimics the tumor microenvironment, namely the mouse Matrigel plug assay loaded with VEGF, bFGF, and S1P, might provide an additional rationale for the use of MEK1/2 inhibitors in cancer therapy. As several major pharmaceutical companies are currently developing MEK1/2 inhibitors for anti-tumor therapy (11), it would be of interest to also investigate tumor lymphangiogenesis in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…50 In lumenal cells, Rab11, Rabin8, and Rab8 colocalize when Rab11 is active. 51 53 and might serve to trigger large and sudden changes in vesicle trafficking associated with early epithelial scattering following HGF stimulation.…”
Section: Molecular Control Of Calcium Influxes Upon Induction Of Epitmentioning
confidence: 99%